Investigating tagasastes' potential for agricultural climate mitigation and adaptation within the context of South Africa - Ord-Armstrong, Leah (Department of Environmental and Geographical Science, 2026)
The need to produce more food for a growing global population has led to the expansion of agriculture and increased land use change, exerting negative impacts on the ecosystem services on which agriculture relies. Given their dependence on ecosystem services, rural communities are especially vulnerable to the effects of climate change and the associated socioeconomic implications. Agricultural strategies are required to alleviate rural poverty, repair the adverse impacts of land degradation and increase food and nutritional security, while addressing the varied requirements and cultural practices of farmers. Agricultural methods such as agroforestry, agroecology and regenerative agriculture are prominent features in developing countries and are increasingly recognized worldwide as avenues to mitigate and adapt to climate change. The agricultural landscape in South Africa is distinguished by a bifurcated agricultural economy, with the majority consisting of small-scale farms primarily functioning at subsistence level, coexisting with major commercial farms accounting for the majority of the country's agricultural output. Limited financial capacity and lack of dietary protein is a major obstacle in small-scale livestock production, while conventional commercial agriculture contributes significantly to land and ecosystem degradation, primarily through the use of chemical fertilizer, pesticides, fungicides and herbicides. This disparity between commercial and small-scale farming creates a complex agricultural setting and presents an opportunity to explore climate-smart sustainable agricultural practices that address the unique challenges of each sector. This paper examines the potential role of the leguminous fodder shrub Chamaecytisus palmensis (tagasaste) to adapt to climate change related challenges in agriculture, while concurrently mitigating agricultural greenhouse gas emissions and facilitating carbon sequestration in South Africa. A sequential data collection strategy was implemented within an integrated mixed methods approach to i) assess the current level of adoption and success of tagasaste use in South Africa; and ii) evaluate the boundaries of tagasaste to intensify agriculture, sequester carbon and adapt to climate change. Primary data from a targeted online survey and personal communications were merged with secondary data from scientific research articles and selected grey literature. The results indicate interest in tagasaste has persisted for over forty years in South Africa, primarily for its potential as livestock fodder. However, its adoption has been limited, largely due to establishment challenges. This contrasts with countries such as Australia and New Zealand, where tagasaste is utilized on a commercial scale and contributes significantly to livestock production. This research demonstrates that tagasaste has a comparatively high capacity for carbon sequestration, while also providing additional environmental and socioeconomic co-benefits. Tagasaste has been found to be hardy to drought conditions, with a favourable water use efficiency. Furthermore, studies show that tagasaste can repair or enhance ecosystem services such as water and nutrient cycles and improves above and below ground biodiversity. Moreover, improved livestock performance through the provision of high protein feed has the potential to support livelihoods as well as food and nutritional security, in both developing and developed regions.